Foreword: SARS-CoV-2 docet - Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2021)
One year has passed since the Sars-CoV-2 infection diagnosis was made in a patient hospitalized in Codogno unveiling the outbreak of coronavirus in Italy and the start of one of the worst pandemics in history. Today, we know a lot more about Covid-19 infection than we did a year ago. We know that the fight against the spread of the virus, when not correctly done, favours the development of variants of the original covid-19 strain and, we also know that these variants especially the one defined as the "English" variant, has the ability to spread much more and more quickly than the original strain. We know that people, even at lethal risk of complications, are especially old aged, but we also know that those who are oligosymptomatic or asymptomatic patients can spread the infection. Grossi E. et al. report in the following pages the results of a research conducted on pregnant women which shows how the risk of contracting the infection is higher in pregnancy although in an asymptomatic form and that the risk is also transmitted to the unborn child. This data makes the report here provided by Intraccolo U. et al. even more interesting according to which the Italian female population tends to excessively medicalise low-risk pregnancies. [...]